The effect of binahong leaf extract on cardiac function in rats fed a high-fat diet - Wahyudi, Dwi Sukma; Sartika, Dewi; Harahap, Alvin Abrar (Jurnal Prima Medika Sains, 2023)
Several antioxidant defense mechanisms protect biological systems from the negative impact of ROS. Natural antioxidants are mainly obtained from plants, such as vegetables, and one of them is the binahong plant which is rich in antioxidants. This plant is often used traditionally as a blood-thinning drug to prevent stroke. This study aimed to evaluate the effect of binahong (anderera cardifolia) leaf extract on cardiovascular health and the histological structure of the heart of wistar male white rats fed a high-fat diet. This study is an experiment with a completely randomized design (CRD) consisting of 4 groups: normal control, treatment 1 dose 200 mg/kg BW, treatment 2 dose 300 mg/kg BW, and treatment 3 dose 400 mg/kg BW. Histopathological data such as aortic wall thickness and number of foam cells were analyzed using SPSS 23 with one-way ANOVA test and Post Hoc LSD at 0.05 significance level. The results showed that administering a dose of 400 mg/kg BW effectively reduced the thickness of the aortic wall and the number of aortic foam cells in rats.